A benchmark for managerial effectiveness. (20th March 2007) - Zimmermann, L.F. 'Bill'; Chanaron, J.J.; Klieb, Leslie
This study presents a tool to gauge managerial effectiveness in the form of a questionnaire that is easy to administer and score. The instrument covers eight distinct areas of organisational climate and culture of management inside a company or department. Benchmark scores were determined by administering sample-surveys to a wide cross-section of individuals from numerous firms in Southeast Louisiana, USA. Scores remained relatively constant over a seven-year timeframe. Techniques for using the benchmark by practitioners are discussed.